Pembuatan Bioplastik Berbahan Bonggol Pisang dengan Penambahan Gliserol - Isnan Prasetya; Siti Hani Istiqomah; Yamtana Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Plastic wastes have serious impact for enviroment and human health. The production of envi-ronmentally friendly plastics (bioplastics) is an alternative to reduce plastic waste which difficult to decompose. Banana tree lump can be utilised as the composite material in bioplastics pro-duction because contains cellulose and starch. Plasticizer substance is required to produce e-lastic plastic. Glycerol is known as best plasticizer compared to other materials. The purpose of the research was to determine the best level of degradation, tensile strength, and elongation value of bioplastics made from banana tree lump flour and glycerol. The experiment employed post test only with control group design. The experiment groups were consisted of three treat-ment groups, i.e. 3:12, 4:12, and 5:12 compositions and one control group; whose composition in each group were 3 gr, 4 gr, 5 gr and 0 gr lump flour with 12 ml of glycerol, respectively. The bioplastics were made by mixing all the materials at temperature of 60-70 0C, and then formed. There were three replications and the data obtained were analysed by using multivariate anova test and LSD test at 0,05 level of signifiance. The results showed that the addition of banana tree lump flour affects the degradation rate, tensile strength and elongation value of the bioplas-tics. The 5;12 composition yielded the the best degradation rate, i.e. 27.88 % every 3 day mea-sured by soil burial test, as well as the best tensile strength (20.08 kg/cm2). While, for elonga-tion value, the control gave the best result, i.e.26.67 %.